IMPROVING STUDENTS’ ENGLISH VOCABULARY MASTERY BY USING INDEX CARD MATCH STRATEGY AT THE SEVENTH GRADE STUDENTS OF SMP NASIONAL PLUS INDO TIONGHOA TARAKAN - Margareta, Margareta; Ulfaika, Romlah (Universitas Borneo Tarakan, 2021)
The aimed of this research is to improve the student’s vocabulary mastery in English by applying index card match strategy in teaching and learning process at the seventh grade students of SMP Nasional Plus Indo Tionghoa Tarakan.This research was use classroom action research (CAR). The research consist of two cycles and each cycle consist of three meetings. The research was conducted on February 05th until 21st, 2020 in SMP Nasional Plus Indo Tionghoa Tarakan. The researcher used all the seventh grade students as the research subject where there are only 32 students of seventh grade. The subject consist of 16 females and 16 males. The technique of collecting the data used observation checklist to observe the teaching and learning process and vocabulary test to check the students’ English vocabulary mastery. The research result showed that the percentage of success students in vocabulary test for the first cycle was 65.6% and the second cycle was 87.5%. Then the observation result showed that the percentage of first cycle was 91% for the teacher and 84.3% for the students and the percentage of the second cycle was 88% for the teacher and 87% for the students. Therefore, it prove that the index card match strategy can improve the students’ English vocabulary mastery at the seventh grade students of SMP Nasional Plus Indo Tionghoa Tarakan.